Status of Height in Relation to Mid Parental Height of Children Having Congenital Heart Disease (The Planet, 2023)
Background: Globally, the incidence of congenital heartdisease is increasing day by day. Congenital heart disease(CHD) is often associated with short stature. The status ofheight in relation to the mid-parental height of childrenhaving congenital heart disease may provide importantclues in managing congenital heart disease (CHD) cases.Aim of the study: This study aimed to assess the status ofheight in relation to the mid-parental height of childrenhaving congenital heart disease. Methods andmaterials: This was an observational cross-sectional studythat was conducted in the Out-Patient Department (OPD)and In-Patient Department (IPD), Combined MilitaryHospital (CMH) from 1st March 2016 to 31st August 2016.In total 50 patients with congenital heart disease (CHD).The data were collected through interviews with a predesigned questionnaire. Results: In this study, among all the cases, 44% were appropriate instature of their height in relation to their parental height and another 56% were short instature in relation to their mid-parental height. It seemed that short stature was stronglyassociated with haemodynamically important congenital heart disease. The frequency ofshort stature was more in cyanotic heart disease. Appropriately treated cases gained catchup growth in spite of having congenital heart disease. Conclusion: The height status ofchildren having CHD is comparatively lower than the expected range. Haemodynamicallyimportant CHD is the mainstay of the cause. Cyanotic heart disease affects height more thanacyanotic disease. Incidence of short stature is observed more in TOF, large VSD and largeASD.
Keywords: Mid-parental height; Children; Congenital heart disease; CHD; Short stature